(untitled) (Spectrum Journal of Innovation, Reforms and Development, 2022)
The article analyzes the measures taken to radically improve the system of spiritual and educational work in the Republic of Uzbekistan. The views of medieval Eastern thinkers focused on the issues of moral education of young people. The philosophical content of Eastern education is revealed. Examples of the ideas of Eastern thinkers on education are given, and their spiritual foundations are studied.